2019
DOI: 10.1371/journal.pone.0209984
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mavoglurant on visual attention and pupil reactivity while viewing photographs of faces in Fragile X Syndrome

Abstract: BackgroundNumerous preclinical studies have supported the theory that enhanced activation of mGluR5 signaling, due to the absence or reduction of the FMR1 protein, contributes to cognitive and behavioral deficits in patients with fragile X syndrome (FXS). However multiple phase 2 controlled trials in patients with FXS have failed to demonstrate efficacy of compounds that negatively modulate mGluR5, including two phase 2b randomized controlled trials (RCT) of mavoglurant (AFQ056, Novartis Pharma AG), when the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…The utility of the emotional faces eye-tracking paradigm assessed in the present study should continue to be evaluated given the wide range of test-retest reliability coefficients reported, in addition to other eye-tracking paradigms that are widely used in the literature that have been shown to consistently distinguish between clinical groups. More recently, a clinical trial utilizing an extended version of the emotional faces paradigm suggested the paradigm was sensitive enough to detect increases in overall looking time, fixations, and pupil reactivity in adolescents and adults with FXS (Hessl et al, 2019). Since many individuals with FXS also receive a co-occurring diagnosis of ASD (Klusek et al, 2014;Talisa et al, 2014;Thurman et al, 2014), the emotional faces paradigm may be sensitive enough to detect a change in treatment trials targeting social and emotional impairments in idiopathic ASD.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of the emotional faces eye-tracking paradigm assessed in the present study should continue to be evaluated given the wide range of test-retest reliability coefficients reported, in addition to other eye-tracking paradigms that are widely used in the literature that have been shown to consistently distinguish between clinical groups. More recently, a clinical trial utilizing an extended version of the emotional faces paradigm suggested the paradigm was sensitive enough to detect increases in overall looking time, fixations, and pupil reactivity in adolescents and adults with FXS (Hessl et al, 2019). Since many individuals with FXS also receive a co-occurring diagnosis of ASD (Klusek et al, 2014;Talisa et al, 2014;Thurman et al, 2014), the emotional faces paradigm may be sensitive enough to detect a change in treatment trials targeting social and emotional impairments in idiopathic ASD.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, it was found that mGluR-LTD at hippocampal CA3:CA1 synapses is exaggerated in Fmr1 KO mice 75 and it was later discovered that in the absence of FMRP, mGluR-LTD no longer requires new protein synthesis 129 . The mGluR-LTD pathway has been targeted in multiple pharmacological studies aimed at developing treatments for FXS 19,[130][131][132][133][134][135][136] , yet we still have a limited understanding of which mRNAs regulated by FMRP are the most important for altered mGluR-LTD phenotypes 19 . mGluR-LTD is central to motor learning tasks mediated by Purkinje cells, evidenced by impairment of conditioned eyeblink responses in global mGluR1 KO mice that can be rescued by Purkinje cell-specific mGluR1 expression 137,138 .…”
Section: Loss Of Function Of Fmrp Causes Altered Behavior and Cognitimentioning
confidence: 99%
“…It is entirely possible that the failure of these trials to demonstrate benefit in their primary endpoint was due to acquired treatment resistance. It is also possible that not all efficacy measures are equally affected by treatment resistance ( Figure 7B ), perhaps explaining why significant improvements could still be observed using other functional measures, notably in subjects receiving the lower drug doses ( 56 ). Regardless, our findings make the case for limiting the duration of continuous treatment, perhaps by providing rest periods, to prevent development of drug resistance that may have masked some benefits of mGluR5 NAMs in previous clinical trials.…”
Section: Discussionmentioning
confidence: 99%